Pollution and ecological risk assessment of antimony and other heavy metals in soils from the world's largest antimony mine area, China. Issue 3 (3rd April 2018) - Long, Jiumei; Tan, Di; Deng, Sihan; Lei, Ming
ABSTRACT: Xikuangshan is located in Lengshuijiang City, Hunan province, China. With intensive mining and metallurgical activities, large amounts of tailing containing heavy metals (in this study, the term "heavy metals" is used for both metals and metalloids) were introduced to the soils around the mine area. Those heavy metals including antimony and other heavy metals would pose huge risk to human health and ecological environment. With a view to providing information on the extent of contamination and potential ecological risk of heavy metals in the soils of this mine area, the total contents of antimony (Sb), manganese (Mn), zinc (Zn), arsenic (As), cadmium (Cd), and lead (Pb) in the soils were examined. The results revealed that the predominant pollutants in this area were Sb, Cd, and Zn with mean concentrations being 356.58, 9.98, and 486.42 mg kg −1, 119.66, 117.41, and 5.17 times of the corresponding background values respectively. The pollution indices (Ps) indicated that the pollution levels of all sampling zones were serious including the control zones. The ecological risk levels of all heavy metals were very high on all the sampling zones except sampling zone 7 (as considerable), and Sb, Cd, and As were regarded as making great contribution to the risk indices (RI).